A Puzzle of Life: Crafting Ribosomal Subunits. Issue 8 (August 2017) - Kressler, Dieter; Hurt, Ed; Baßler, Jochen
Abstract : The biogenesis of eukaryotic ribosomes is a complicated process during which the transcription, modification, folding, and processing of the rRNA is coupled with the ordered assembly of ∼80 ribosomal proteins (r-proteins). Ribosome synthesis is catalyzed and coordinated by more than 200 biogenesis factors as the preribosomal subunits acquire maturity on their path from the nucleolus to the cytoplasm. Several biogenesis factors also interconnect the progression of ribosome assembly with quality control of important domains, ensuring that only functional subunits engage in translation. With the recent visualization of several assembly intermediates by cryoelectron microscopy (cryo-EM), a structural view of ribosome assembly begins to emerge. In this review we integrate these first structural insights into an updated overview of the consecutive ribosome assembly steps. Trends: Cryoelectron microscopy analyses of the 90S preribosome show that the biogenesis factors create a casting mold that encloses the nascent pre-40S subunit. Structures of nuclear pre-60S particles reveal that accommodation of the 5S ribonucleoprotein into its final position involves major structural rearrangements of the central protuberance. Moreover, within the 'foot' region the internal transcribed spacer (ITS) 2 rRNA is bound by several biogenesis factors that coordinate ITS2 processing. An increasing number of biogenesis factors can be viewed as checkpoint factors sensing the successful completion of assembly events before licensing preribosomes for the subsequent maturation steps. Supplying all ribosomal building blocks in stoichiometric amounts is a highly regulated process. Several dedicated chaperones contribute to the production of assembly-competent ribosomal proteins (r-proteins). Excess r-proteins are degraded via the excess r-protein quality control pathway.